PERANCANGAN DAN IMPLEMENTASI LOAD BALANCING REVERSE PROXY MENGGUNAKAN HAPROXY PADA APLIKASI WEB - Ari Budi Noviyanto; Erna Kumalasari N; Amir Hamzah (Jurnal Jarkom, 2015)
Servers are computers for computer center managers and the other. Many more client could make server have a hard woking. this situation will make the web serverperformance has decrease and making the access to the server will be difficulty because the server was busy or time-out. another problem is a down server or server failure. that is the problem that we must be avaoided. To overcome these problems, merging severalserversinto a single unitthat can worksimultaneouslyforload balancingserveris the solution. One method that is meaningful is using load balancing or even distribution of a burden ( request ) on the web server aims to relieve a burden is borne each server. In the process load balancing any one kind of load balancer is HAProxy, HAProxy is a software load balancer to the application of tcp and http who support a need a counterweight burden.Haproxy have the ability to control traffic of each request data from clients and showing statistics from on use each web server that it can controlling. Design and implementation of haproxy as balancer reverse a proxy be able to address the problems caused by burden excessive traffic because haproxy divide the expense request that goes into server haproxy so that the use of haproxy as load balancer can overcome the problems because the distribution of the burden known to second server backend.